(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The paper presents the results of studying one of the urgent worldview problems - the problem of the origin of man, the stages of formation and evolutionary development of his material and spiritual culture, determining the periods of initial habitation on the territory of the northern slopes of High Asia and adjacent regions. The results of studying the most ancient anthropogenic deposits showed that the territory of the Tien Shan, Pamir- Alai mountain systems was settled by the human ancestor within 1.5 million years ago. As a result of many years of research, the sites of the early Anthropogen in the region of research have gained worldwide fame and taken a worthy place in the world history of the origin of the most ancient material cultures. Original assessments of the emerging methodological developments in the study of the history of the early Anthropogen are based on the actual results and logic of the interpretation of "non-standard" scientific positions, as well as the receipt of new materials on and constantly growing information on the history of the early Anthropogen.